Interannual fluctuations in copepod abundance and contribution of small forms in the Drake Passage during austral summer - Thompson, Gustavo Ariel (2012)
The relative importance of small forms of copepods has been historically underestimated by the traditional use of 200-300-μm mesh nets. This work quantified the distribution and abundance of copepods, considering two size fractions (<300 μm and >300 μm), in superficial waters (9 m deep) of the Drake Passage and contributed to the knowledge of their interannual fluctuations among three summers. Four types of nauplii and eleven species of copepods at copepodite and adult stages were identified, with abundance values of up to 13 ind L -1 and 28,300 μg C m -3. The <300-μm fraction, composed of Oithona similis, small cyclopoids and nauplii, dominated the copepod communities in the 3 years; it accounted for more than 77% of the total number and for between 40 and 63% of the total biomass. Changes in density and biomass values among the three cruises differed according to copepod size fraction and water mass; the >300-μm fraction showed no changes among the 3 years, both in Antarctic (density and biomass) and in Subantarctic waters (density), whereas the <300-μm fraction showed higher (density and biomass) values in 2001 both in Subantarctic and in Antarctic waters. Sea surface temperature and its anomaly accounted for the largest proportion of variability in copepod density and biomass, particularly for the <300-μm fraction.